A review of policies relating to speech and language development of children in the philippines - Latore, Angelica Anne E.; Rivera, Ana Kriselda; Quitiquit, Paul Adlai B.; Antonio, Carl Abelardo T. (2017)
This paper was a review of current initiatives in the field of speech and languages development (SLD) of Filipino children. In general, the national policies related to SLD have focused on language in education (58%), prevention of language development disorders (17%), and provision of equal rights for with disabilities (8%). The Universal Newborn Hearing Screening and Intervention Act of 2009 is a relatively new policy that still needs to be thoroughly introduced to many healthcare practitioners. Meanwhile, the integration of the native language as medium of instruction under the Enhanced Basic Education Act of 2013 creates significant concerns among teachers and parents. On the other hand, the Magna Carta for Disabled Persons lacks specific provisions for children with language problems. Major barriers to successful implementation include lack of awareness and understanding of the rationale of policies, accessibility problems, and limited financial coverage of services.
Keywords: Speech and Language -- Development